2019
DOI: 10.3855/jidc.11355
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence associated genes in Campylobacter jejuni isolated from chicken in Côte d’Ivoire

Abstract: Introduction: Campylobacter jejuni is one of the major causes of gastroenteritis worldwide of the last century. The aim of this study was to investigate the antibiotics profiles and the virulence gene in C. jejuni strains isolated from chicken in Côte d’Ivoire. Methodology: A total of 336 chicken ceaca samples recovered from market of two municipality of Abidjan were examined by conventional microbiological methods and molecular test using PCR. The antibiotic susceptibility tests of the isolates were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Our study revealed a significant prevalence of Campylobacter spp in poultry feces (67.96%) and in retail poultry carcasses (50%). These frequencies are consistent with those reported in previous studies conducted in Sri Lanka (Kottawatta et al., ) and in Ivory Coast (Goualié et al., ). Conversely, a higher prevalence of Campylobacter was observed in poultry carcasses in Japan (Furukawa et al., ), in Maryland (Cui, Ge, Zheng, & Meng, ), and in poultry feces in the Netherlands (Schets et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study revealed a significant prevalence of Campylobacter spp in poultry feces (67.96%) and in retail poultry carcasses (50%). These frequencies are consistent with those reported in previous studies conducted in Sri Lanka (Kottawatta et al., ) and in Ivory Coast (Goualié et al., ). Conversely, a higher prevalence of Campylobacter was observed in poultry carcasses in Japan (Furukawa et al., ), in Maryland (Cui, Ge, Zheng, & Meng, ), and in poultry feces in the Netherlands (Schets et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…jejuni was the most prevalent with 70% rate in poultry feces and 100% in carcasses. Similar results were also reported in studies conducted in Ivory Coast (Goualié et al., ) and in Brazil (Perdoncini et al., ). In contrast, in Asia and Thailand, two studies revealed a higher percentage of C. coli than C. jejuni (Kottawatta et al., ; Padungtod & Kaneene, ).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies using AST performed worldwide corroborated the present work and also showed that C. jejuni strains are resistant to ciprofloxacin, tetracycline, and erythromycin. [25][26][27][28][29] Duarte et al 27 studied 89 C. jejuni strains isolated from humans, animals, and food and observed resistance to ciprofloxacin, tetracycline, and erythromycin in 82, 59, and 6 strains, respectively. Fifteen of the 39 C. jejuni strains isolated from poultry in Côte d'Ivoire were resistant to ciprofloxacin, and seven strains were resistant to erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of the 39 C. jejuni strains isolated from poultry in Côte d'Ivoire were resistant to ciprofloxacin, and seven strains were resistant to erythromycin. 25 A study performed in three regions of Peru evaluated the ciprofloxacin resistance of C. jejuni strains isolated from humans in two different periods. These authors observed a significant increase in the resistant strains in all the regions, including 72.6% to 82.8% in Cusco, 24.1% to 48.9% in Iquitos, and 73.1% to 89.8% in Lima.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections are mostly involved in causing diseases in sub-Saharan countries. Goualié et al (2019) reported the high incidence of multidrug resistant bacteria in chickens in Cote d'Ivoire. This problem is emergent because of the misuse of drugs and the free accessibility to drugs in human or in animal trials.…”
Section: Introductionmentioning
confidence: 99%